2022
DOI: 10.3389/fimmu.2022.839167
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Signature and Potential Application of Serum Polyunsaturated Fatty Acids Metabolism in Patients With Vitiligo

Abstract: Vitiligo is a depigmented skin disorder caused by a variety of factors, including autoimmune, metabolic disturbance or their combined effect, etc. Non-targeted metabolomic analyses have denoted that dysregulated fatty acids metabolic pathways are involved in the pathogenesis of vitiligo. However, the exact category of fatty acids that participate in vitiligo development and how they functionally affect CD8+ T cells remain undefined. We aimed to determine the difference in specific fatty acids among vitiligo pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…A case control study from Turkey discovered that an increased percentage in the affected BSA were determined to be independent predictors of metabolic syndrome 26 . Our recent study has indicated that the severity of vitiligo is significantly associated with abnormal accumulation of metabolite 27 . Thus, we speculate that metabolic imbalance may be a potential cause for DM occurrences in patients with vitiligo, which needs further study.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…A case control study from Turkey discovered that an increased percentage in the affected BSA were determined to be independent predictors of metabolic syndrome 26 . Our recent study has indicated that the severity of vitiligo is significantly associated with abnormal accumulation of metabolite 27 . Thus, we speculate that metabolic imbalance may be a potential cause for DM occurrences in patients with vitiligo, which needs further study.…”
Section: Discussionmentioning
confidence: 80%
“…26 Our recent study has indicated that the severity of vitiligo is significantly associated with abnormal accumulation of metabolite. 27 Thus, we speculate that metabolic imbalance may be a potential cause for DM occurrences in patients with vitiligo, which needs further study.…”
Section: Discussionmentioning
confidence: 86%
“…Vitiligo is the most commonly acquired complex disorder of pigmentation, with a prevalence of ~1% in the world population (Ezzedine et al, 2015 ; Ye et al, 2022 ; Yu et al, 2022 ). It is characterized by well-circumscribed depigmented macules and patches that result from a progressive loss of functional melanocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Oral supplementation with ARA is not expected to lead to serum and tissues ARA concentrations higher than 50 μM for a brief period because albumin specifically binds to fatty acids. This rapidly reduces the concentration of free fatty acids to below 0.1 μM while permitting far higher concentrations, from 20 μM to >3 mM, to be stabilized in blood and tissues [ 29 , 30 , 31 , 32 , 33 ]. Of note, in vitro exposure to 50 μM ARA does not impair T cell viability [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…This rapidly reduces the concentration of free fatty acids to below 0.1 μM while permitting far higher concentrations, from 20 μM to >3 mM, to be stabilized in blood and tissues [ 29 , 30 , 31 , 32 , 33 ]. Of note, in vitro exposure to 50 μM ARA does not impair T cell viability [ 33 ]. Accordingly, we opted for 30 min exposure of tumor and normal cell lines to fetal calf serum-free medium supplemented with 50 μM ARA to investigate the ARA tumoricidal mechanism(s).…”
Section: Introductionmentioning
confidence: 99%